A pulsed high-current plasma beam under external and self-induced magnetic confinement in a linear device. (22nd August 2019) - Zheng, X J; Gou, F J; Zhou, Y; Wang, H X; Wallace, A C; Wang, H B; Huang, Z H; Ji, X Q; Liang, S Y; Liu, W; Feng, Y T; Deng, B Q
Abstract: The previously developed governing equations for Magnetic Inertial Confinement Fusion, which combines the advantages of both magnetic and inertial confinement approaches, are improved to analyse a plasma beam in a linear device assisted by an external magnetic field. The equations are applied to simulate a steady state plasma beam sustained by a DC power supply as well as a transient beam generated by a separate pulsed discharge superimposed on the steady-state plasma. The calculated increase of plasma density during the pulse from the steady-state condition is compared with measurements using a laser interferometer at a relatively low voltage supply of 150 V for the pulses. The numerical and test results are found to agree within 20%. When the voltage rises, plasma instability is observed. This issue is inherent due to the use of a solid positive target electrode that blocks the plasma flow in the axial direction. As a remedy, additional tests were carried out using a hollow target electrode in a two-circuit design (to permit free gas flow in the axial direction) by replacing the DC power with transient, pulsed, high-voltage sources for plasma initiation and beam formation. These enhancements were successful in suppressing the instabilities. The peak plasma density was calculated at ∼10 22 m −3 for confinement times of the order of 1 ms. These results lie between the extremes for the current leading approaches yet are achieved for a more compact and inexpensive linear device.